PENGARUH PEMBERIAN TERAPI MUSIK TERHADAP PENURUNAN INTENSITAS NYERI PADA PASIEN POST SECTIO CAESAREA - Herri Novita Br Tarigan; Megawati Sinambela; Reka Novrina (Jurnal Penelitian Keperawatan Medik, 2020)
The World Health Organization (WHO) sets the average standard of sectio caesarean delivery in a country to be around 5-15 percent per 1000 births in the world.In Indonesia, the results of Basic Health Research in 2013 showed births with a caesarean section of 9.8% out of a total of 49,603 births from 2010 to 2013. Nursing problems that often arise in cases of post sectio caesarea are pain caused by trauma to the tissue due to tissue damage and direct irritation to the receptors. The nurse's independent action to control the pain felt by the patient is to do pain management with non-pharmacological techniques, namely music therapy. The purpose of this study was to determine the effect of music therapy on pain intensity reduction in post sectio caesarea patients. This study used a quasi-experimental design method with a non equivalent control group design. The sampling technique uses accidental sampling technique with a total sample of 32 respondents, 16 experimental groups and 16 control groups. This study used the Wilcoxon non-parametric test. The results of this study indicate the P-value (0.001) <α (0.05). The conclusion of this study is that there is an effect of music therapy on the decrease in pain intensity in post-sectio caesarea patients in the hybrid room Sembiring General Hospital.